Books, book reviews, anoles, and do we really know what we believe we know? - Mccranie, James R. (Zootaxa, 2017)
McCranie & Köhler (2015, hereafter M&K) recently published a book on the systematics, distribution, and conservation of the anoles (Squamata: Dactyloidae) of the Central American country of Honduras. Those authors included 39 species placed in two genera. Gray (2015; hereafter G) published a largely well-done review of that book. However, G made a few incorrect statements, some of which I feel need to be addressed. In addition, the anole systematics at the species, and especially at the generic level, are extremely contentious issues that affect anyone trying to publish any manuscript regarding anole systematics.